2018
DOI: 10.19173/irrodl.v19i2.3440
|View full text |Cite
|
Sign up to set email alerts
|

Goal Orientation and Academic Performance in Adult Distance Education

Abstract: Research has shown the importance of goal orientation in predicting academic performance for children, adolescents, and college students in traditional educational settings. Studies on this relationship within adult distance education, however, are lacking. To fill this gap, the present study was conducted to investigate the relationship between goal orientation and academic performance in adult distance learners. A sample of N = 1128 distance university students (age 18-75 years) filled out an online question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…However, there are also several studies that identified different relationships. Neroni, Meijs, Leontjevas, Kirschner, and De Groot (2017) for example, discovered that mastery approach goals were no significant predictor of student success, measured as achievement, for the distant education students in their sample. One possible explanation they give for this lack of a relationship is that distant education students with a mastery orientation possibly are not driven by grades at all, and only enrol in the courses for their own interest, subsequently not participating in the final exams.…”
Section: Discussionmentioning
confidence: 98%
“…However, there are also several studies that identified different relationships. Neroni, Meijs, Leontjevas, Kirschner, and De Groot (2017) for example, discovered that mastery approach goals were no significant predictor of student success, measured as achievement, for the distant education students in their sample. One possible explanation they give for this lack of a relationship is that distant education students with a mastery orientation possibly are not driven by grades at all, and only enrol in the courses for their own interest, subsequently not participating in the final exams.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, it was shown by a mixed model regression that there was no significant relationship between academic success and mastery goal orientation (Neroni et al, 2018). By the same token, Ugur (2016) reported that academic performance is not significantly predicted by mastery goal orientation.…”
Section: Goal Orientations and Academic Achievementmentioning
confidence: 87%
“…In that regard, research carried out in the context of MOOCs (i.e., another example of open higher online education), demonstrated that intention is an important requisite for completion (Henderikx et al, 2017). Besides that, although performance approach goals (i.e., whether or not students' are oriented at outperforming others) might not relate to completion, they appear predictive for other correlates of students' success, such as grade point average (Neroni et al, 2018). Furthermore, in the present study, no association was found between volition (i.e., consequence control and metacognition) and completion.…”
Section: Discussionmentioning
confidence: 99%